SOSIALISASI PEMBIAYAAN SYARIAH PRODUK MURABAHAH DI DESA SUKAMAJU, KECAMATAN JONGGOL, KABUPATEN BOGOR - Rully Trihantana; Miftakhul Anwar; Nanda Suganda (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
This community service program intends to provide socialization to the community in Sukamaju Village, Jonggol District, Bogor Regency, regarding Islamic financial institution products, especially murabaha products. The method used is to socialize to community groups, and it is held at the homes of socialization participants. The purpose of this community service is to educate the public about sharia financing products that are most in demand, namely murabahah products. As a result, the community begins to understand the product in question and begins to make decisions to carry out financial transactions at Islamic financial institutions in general with contracts that are in accordance with Islamic law, namely murabahah contracts.